Pasolini and Foucault analyze power in contemporary democracies - López-Pérez, Sheila (Anales del Seminario de Historia de la Filosofía, 2026)
The objective of this work is to analyze power in contemporary democracies based on Pasolini and Foucault. To do this, a review will be carried out of the texts - and films, in the case of the filmmaker - of the authors who address the topic and which will allow us to draw a bridge between them. We will focus on his description of power as the ability to instrumentalize the other and relate it to the “circular power” of the elites, a power completely removed from the intervention of the people. We will locate this type of power as the main tool of contemporary capitalism, which is supported by a system of representative democracies that only corroborate the distancing of power resources from citizens. Next, we will present the subjectivation of citizens, that is, their conversion into political actors, as the only way to take charge of their democracies. Finally, we will raise the need to create a trans-democratic globalization that can reverse the economic globalization -based on the circular power of the elites- that governs today.
Keywords: democracy; Foucault; instrumentalization; Pasolini; power; subjectivation